Design of in-plane torsion experiment to characterize anisotropic plasticity and fracture under simple shear. (1st February 2022) - Grolleau, Vincent; Roth, Christian C.; Mohr, Dirk
Abstract: A novel experimental set-up is proposed to perform in-plane torsion experiments on grooved disk specimens. As compared to previously proposed systems, an enhanced clamping system is introduced to enable the torsion testing of high strength materials such as dual phase steels. The clamping is achieved without applying the clamping pressure through an axial actuator. Instead a custom-made washer-nut system is used which allows for the monitoring of the entire specimen front surface with cameras. Experiments are performed on three different steels (DC01, DP980, AISI301) to demonstrate the validity of the technique for measuring the stress–strain curve for strains of up to 2, for strain rate jump testing, for cyclic loading and for fracture testing. In particular, the demonstration experiments elucidate the importance of full field strain measurements during in-plane torsion. The strain fields vary along the gage section circumference in a periodic manner that is related to the anisotropy of the tested material. This important observation is confirmed through a finite element study covering a wide range of anisotropic Hill'48 materials with non-associated plastic flow.